Junior High School Students' Proportional Reasoning Ability in the Domain Comparison: A Gap in Results Between Indicators - Lutfi, Ahmad; Dahlan, Jarnawi Afgani; Martadiputra, Bambang Avip Priatna; Jupri, Al; Rusyid, Husnul Khatimah; Mukhibin, Ahmad (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
The purpose of this study was to analyze students' proportional reasoning ability. The research subjects consisted of 21 students of VIII class in one of the public junior high schools in Semarang City who had obtained comparison materials (ratio and proportion). Data collection used test instruments that were developed based on indicators of proportional reasoning ability consisting of 6 questions. The data were analyzed qualitatively with data reduction analysis procedures, data presentation, and conclusion drawing/verification. The results showed that (1) none of the students met all the indicators of proportional reasoning ability, namely the ability to understand proportional relationships, solve proportional problems of missing values, numerical comparisons, qualitative predictions, distinguish proportional and non-proportional problems, and solve proportional relationships of inverse values, (2) all students have been able to understand proportional relationships, but they are still very limited in their ability to distinguish proportional and non-proportional problems, and solve proportional relationships of inverse value, and (3) the strategy most often used by students to solve proportional reasoning problems is the cross-multiplication strategy.